2017
DOI: 10.1108/jedt-09-2015-0053
|View full text |Cite
|
Sign up to set email alerts
|

Design-oriented strategy typology and innovation framework

Abstract: Purpose Using Taiwanese enterprises that produce computer and consumer electronics products as case subjects, this study aims to explore the effective product innovation strategies applied to cope with competition in the global market and develop a competitive advantage. The product design strategies and methods of companies that used different types of innovation strategies were then analyzed. Finally, a mapping framework for product innovation and design strategies was proposed for enterprises in the compute… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…By integrating Kelley's design strategy factors, Teng identified 10 strategic attributes and defined design strategy as a series of product design strategy attributes related to decision making to achieve product design innovation goals and provide a firm with the unique design competitive advantage it needs. Therefore, design strategy is a way to achieve product innovation goals, analyze customer needs and competitor influence, match the core competencies of the company's research and development, and execute tasks through a design team to achieve the company's performance goals [46].…”
Section: Design Strategymentioning
confidence: 99%
See 2 more Smart Citations
“…By integrating Kelley's design strategy factors, Teng identified 10 strategic attributes and defined design strategy as a series of product design strategy attributes related to decision making to achieve product design innovation goals and provide a firm with the unique design competitive advantage it needs. Therefore, design strategy is a way to achieve product innovation goals, analyze customer needs and competitor influence, match the core competencies of the company's research and development, and execute tasks through a design team to achieve the company's performance goals [46].…”
Section: Design Strategymentioning
confidence: 99%
“…Borowski [55] suggests that innovation strategies can help to encourage, motivate, stimulate, and achieve technological or service progress. Many studies have also shown that innovation strategies help firms to differentiate themselves from their competitors by offering unique products or services to their customers [46,56]. Therefore, scholars generally believe that innovation strategies help firms to pursue superior performance with higher brand equity, gain better partners, and attract highly skilled personnel by setting more ambitious goals [57,58].…”
Section: Innovation Strategymentioning
confidence: 99%
See 1 more Smart Citation
“…Of the 18 product design strategies revealed by Hsu's (2017) study, the consistent keys to success can be crystallized down to the following six design strategies most commonly applied to build innovation into products:…”
Section: Analyzing Customer Needs and Competitor Activitymentioning
confidence: 99%
“…The review is based on "Design-oriented strategy typology and innovation framework" by Hsu (2017). This case study of Taiwanese consumer electronics and computer companies demonstrates how product innovation strategies are being used to develop a competitive advantage that survives in the global market.…”
Section: Maneuvering Through Competitive Watersmentioning
confidence: 99%